2001
DOI: 10.1074/jbc.m010627200
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor Type 2 Contains mRNA Instability Elements within Exon 4 of the Coding Region

Abstract: Plasminogen activator inhibitor type 2 (PAI-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…The analyses of the chimeric mRNAs identified the cis-element in the region corresponding to the ORF. There have been several reports that showed the determinants for mRNA stability in the coding region (45)(46)(47).…”
Section: Fig 7 Ib-mrna Was Stabilized In Response To Lps or Il-1␤ Bmentioning
confidence: 99%
“…The analyses of the chimeric mRNAs identified the cis-element in the region corresponding to the ORF. There have been several reports that showed the determinants for mRNA stability in the coding region (45)(46)(47).…”
Section: Fig 7 Ib-mrna Was Stabilized In Response To Lps or Il-1␤ Bmentioning
confidence: 99%
“…Our previous REMSA studies using HT-1080 cells have shown that a number of cellular factors recognize the PAI-2 AU-rich element and during PMAϩTNF treatment a transient increase in the binding activity of one particular mRNAbinding protein is observed (34). The time course of this transient increase in binding activity parallels the accumulation of TTP mRNA in the same cells (data not shown) raising the possibility that the transiently induced PAI-2 mRNA-binding protein is TTP itself.…”
Section: Ttp Expression Correlates With Reduced Levels Of Pai-2mentioning
confidence: 79%
“…The TTP mammalian expression plasmid CMV.hTTPtag (31) (hereafter referred to as pTTP-HA) was provided by Dr. Paul Bohjanen (University of Minnesota). The wild-type PAI-2 expression plasmid pCI-PAI-2 contains the 1872-bp PAI-2 cDNA (9) inserted into the EcoR1 site of the expression plasmid pCl-neo (Promega, Madison, WI) (34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations